MINI-SURGICAL TREATMENT FOR ACUTE CHOLECYSTITIS - Saydullaev Z.Y.; Davlatov S.S; Jurayev A.A (Scholar Express Journals, 2025)
Cholelithiasis occupies one of the first places among surgical diseases. Materials and methods. The results of surgical treatment of 138 patients with acute cholecystitis were analyzed. The age of the patients ranged from 18 to 89 years; women predominated - 84.8%. The preoperative diagnosis of acute cholecystitis was made based on clinical evaluation, laboratory data, and radiological signs of acute cholecystitis.
Keywords: cholelithiasis; acute calculous cholecystitis; cholecystectomy; drainage of the choledochus